Analisa Wacana Pemberitaan Kasus Korupsi E-KTP Pada Media Kompas.com Terhadap Pembentukan Opini Publik: Universitas Islam Riau - Neri Widya Ramailis; Dede Nopendri (SISI LAIN REALITA, 2019)
Discourse is a series of sentences that relate and connect one proposition with the other propositions to from a unity. The main function of the news is not to warn, instruct, and make the public stunned, the main function of the news is to inform and then it is upto the public to utilize the news. There are two ways for the news to be useful to the public, the first to effort news as general knowledge and the second to effort the news a tool of social control. E-Ktp corruption cases are one of the biggest corruption cases that occurered in Indonesia. Therefore, many mass media reported heavilly on E-Ktp corruption cases, one of which was the kompas.com. furthermore, to find out how the writer gets the source the writer gets the source of data and information the writer uses the criminology visual method and then analyzes it using criminology newsmaking theory. However, the results of this study illustrate that the aspect highlighted are those of actors suspected of being involved in E-Ktp corruption cases. Where the media only emphasizes one institution, namely the people’s representative council, even though in this case the involved parties are not only the legislature but case the involved parties are not only the legislature but also from various institutions such as the interior ministry, state-owned enterprises, and private entrepreneurs. In the aspect of media projection Kompas.com make the bulk of the news about E- Ktp corruption cases as news headline and a tranding topic.